Infeksi Jamur Dermatofita Pada Penderita Mikosis Kuku - Winda Irawati Zebua; Kiki Nurtjahja; Sartini Sartini (Universitas Medan Area, 2021)
Dermatophytes are a group of fungi that cause nail abnormalities. This study aims to determine dermatophyte fungal infections in patients with nail mycoses. The method used in this study is descriptive and the sample was taken by purposive sampling with the criteria of damaged toenails, with characteristics: nails are not shiny, brownish to black from the base to the tip then the nails are examined directly with 10% KOH and cultured using media Sabouraud Dextrose Agar (SDA). The fungi isolated on slanted agar containing SDA and each fungal species were then identified using preparations for microscopic examination. The results showed that from 30 samples, 8 (eight) nail samples were positive for dermatophytes, namely: 5 (five) people infected with the fungus Tricophyton mentagrophytes species, 2 (two) people infected with the Trichophyton rubrum fungus, and 1 (one) person infected with Epidermophyton floccosum..